TINGKAT PENGETAHUAN SISWA/SISWI SMA MUHAMMADIYAH 01 MEDAN TERHADAP PENURUNAN KETAJAMAN PENGLIHATAN - Maysaroh Ritonga Ritonga; Maysaroh Ritonga; dr. Zaldi Sp.M (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
Background:Knowledge is important for choosing actions to be taken as in the case of learning and teaching. Refractive negligence is the most common eye disorder, occurring when we cannot focus our eyes clearly on an open area, making a person's vision blurred. There are several factors that play a role in the occurrence of refractive disorders, namely environmental factors that play an important role in the occurrence of refractive disorders such as the habit of doing activities at close range, including reading, using a computer and playing video games. Objective: this study was to determine the level of knowledge of students of Muhammadiyah 01 Medan High School on the decrease in visual acuity. Method: The type of research used is observational analytic descriptive research with cross-sectional design. Results: A total of 44 male respondents, 4 with insufficient knowledge, 7 with sufficient knowledge and 33 with good knowledge. There were 42 female respondents, 1 respondent with insufficient knowledge, 7 with sufficient knowledge and 34 with good knowledge. Conclusion: the level of knowledge of students of class XII of Muhammadiyah 01 Medan High School on the improvement of visual acuity in general in either category.